Comprehensive evaluation of water resources and environmental carrying capacity based on dualistic water cycle analysis and its application in the Tuo River Basin, China. (February 2023) - Peng, Jiayu; Tong, Hongjin; Liu, Xiaocong; Feng, Yu; Zhu, Yumeng; Wu, Yu; Chu, Zhaosheng; Zheng, Binghui
Highlights: WRECC indicators were selected from dualistic water cycle analysis and represented a reciprocal relationship between humans and nature. Insufficient natural river base flow and wastewater collection rate were key water environmental issues. Strategies for increasing recycled water use and sewage treatment efficiency were proposed to promote WRECC. Abstract: Maintaining water quantity and quality are two problems that occur during water resource development. Considering the reciprocal relationship, the threshold of water resource development urgently needs to be evaluated to guarantee environmental water function. In this study, the water resources and environmental carrying capacity (WRECC) evaluation method was proposed based on dualistic water cycle analysis. Nine indicators from 4 aspects, including the water resource utilization proportion, water use efficiency, pollutant treatment efficiency, river flow, and mutual coupling in the dualistic water cycle processes, were selected to represent the comprehensive WRECC. The first-order tributary of the Yangtze River, the Tuo River Basin, was chosen to validate the method. During the year 2009 to 2018, the water environment quality was improving in the study area, and WRECC evaluation results were in accordance with the change in the water system, which showed a decreasing trend during the study periods. WRECC revealed that the upstream area had severer water pressure than the middle area, mainly coming from insufficient freshwater to support social development and provide dilution capacity. The study proposed a human water cycle intervention scenario by increasing the recycled water use rate and wastewater treatment rate to improve the WRECC, and the improvement effects can reach 30%. The WRECC method provides a useful tool for water environment management and water resource planning.